The Effect of Synthetic Estrogen on Hepar Stucture And Level of SGOT and SGPT of Balb’C Female Mice (UMus musculus) - Susantin Fajariyah; Eva Tyas Utami; Yunita Arisandi (Jurnal ILMU DASAR, 2010)
The objectives of this study were to observe the effect of synthetic estrogen (diethylstilbestrol/DES) on hepar structure and level of SGOT as well as SGPT of female mice (Mus musculus). Mice were gavage by DES dose 0.084 μg/g bb, 0.168 μg/g bb, 0.336 μg/g body weight, sesame oil and control. DES was treated by gavage for 15 days. Observation were performed liver structure contain of number of normal hepatocyte, and hepatocyte disruption (picnosis, vacuole cell, and necrosis), also SGOT-SGPT level. The result showed that DES effected to the disruption of hepatocyte particularly necrosis was relativity high in 0,168 μg/g bb DES treatment. SGOT and SGPT level on blood increased after DES treatment.